Recommendation to test limonene hydroperoxides 0·3% and linalool hydroperoxides 1·0% in the British baseline patch test series. (1st December 2017) - Wlodek, C.; Penfold, C.M.; Bourke, J.F.; Chowdhury, M.M.U.; Cooper, S.M.; Ghaffar, S.; Green, C.; Holden, C.R.; Johnston, G.A.; Mughal, A.A.; Reckling, C.; Sabroe, R.A.; et al.
Summary: Background There is a significant rate of sensitization worldwide to the oxidized fragrance terpenes limonene and linalool. Patch testing to oxidized terpenes is not routinely carried out; the ideal patch test concentration is unknown. Objectives To determine the best test concentrations for limonene and linalool hydroperoxides, added to the British baseline patch test series, to optimize detection of true allergy and to minimize irritant reactions. Methods During 2013–2014, 4563 consecutive patients in 12 U.K. centres were tested to hydroperoxides of limonene in petrolatum (pet.) 0·3%, 0·2% and 0·1%, and hydroperoxides of linalool 1·0%, 0·5% and 0·25% pet. Irritant reactions were recorded separately from doubtful reactions. Concomitant reactions to other fragrance markers and clinical relevance were documented. Results Limonene hydroperoxide 0·3% gave positive reactions in 241 (5·3%) patients, irritant reactions in 93 (2·0%) and doubtful reactions in 110 (2·4%). Linalool hydroperoxide 1·0% gave positive reactions in 352 (7·7%), irritant reactions in 178 (3·9%) and doubtful reactions in 132 (2·9%). A total of 119 patients with crescendo reactions to 0·3% limonene would have been missed if only tested with 0·1% and 131 patients with crescendo reactions to 1·0% linalool would have been missed if only tested with 0·25%. In almost two‐thirds of patients with positive patch tests to limonene and linalool the reaction was clinically relevant. The majority of patients did not react to any fragrance marker in the baseline series. Conclusions We recommend that limonene hydroperoxides be tested at 0·3% and linalool hydroperoxides at 1·0% in the British baseline patch test series.